1990
DOI: 10.1159/000243302
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and Total Parenteral Nutrition of the Neonate

Abstract: The newborn is dependent upon fat for energy production. Fatty acid oxidation requires the cofactor carnitine. The preterm infant is born with limited carnitine reserves. During total parenteral nutrition (TPN) plasma and tissue carnitine concentrations decrease indicating that rates of carnitine biosynthesis are inadequate. The ability of the premature infant to oxidize fatty acids is related to the carnitine status. Several studies suggest an improvement of fatty acid oxidation after a fat challenge if TPN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
2
14
0
2
Order By: Relevance
“…Carnitine is a key cotransporter for efficient uptake of fatty acids into the mitochondria for -oxidation. Our results confirm earlier reports that the decreased circulating carnitine levels in TPN-fed infants reflect low carnitine stores and inadequate capacity for carnitine biosynthesis (54). We measured the carnitine content of the diet of ENT piglets (53.95 nmol/g diet) and found that the concentration in the plasma of these piglets was higher than what could be achieved from the diet alone.…”
Section: Discussionsupporting
confidence: 90%
“…Carnitine is a key cotransporter for efficient uptake of fatty acids into the mitochondria for -oxidation. Our results confirm earlier reports that the decreased circulating carnitine levels in TPN-fed infants reflect low carnitine stores and inadequate capacity for carnitine biosynthesis (54). We measured the carnitine content of the diet of ENT piglets (53.95 nmol/g diet) and found that the concentration in the plasma of these piglets was higher than what could be achieved from the diet alone.…”
Section: Discussionsupporting
confidence: 90%
“…It is well established that the fetus has limited ability to synthesize carnitine: during total parenteral nutrition, plasma carnitine decreases in premature infants and tissue accretion of carnitine declines (30). In the cord blood, the entire carnitine ester spectrum could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuses and neonates do not have the ability to convert g-butyrobetaine to carnitine. Therefore, in contrast to adulthood, l-carnitine supplementation is essential for fetuses and neonates whose source of carnitine is placenta and breast milk, respectively [33]. Soy-based and cow's milk-based infant formulas also contain carnitine.…”
Section: Carnitine: Biosynthesis Physiological Roles and Nutritionalmentioning
confidence: 99%